2018
DOI: 10.1105/tpc.18.00250
|View full text |Cite
|
Sign up to set email alerts
|

Two Abscisic Acid-Responsive Plastid Lipase Genes Involved in Jasmonic Acid Biosynthesis in Arabidopsis thaliana

Abstract: Chloroplast membranes with their unique lipid composition are crucial for photosynthesis. Maintenance of the chloroplast membranes requires finely tuned lipid anabolic and catabolic reactions. Despite the presence of a large number of predicted lipid-degrading enzymes in the chloroplasts, their biological functions remain largely unknown. Recently, we described PLASTID LIPASE1 (PLIP1), a plastid phospholipase A that contributes to seed oil biosynthesis. The genome encodes two putative PLIP1 paralogs, which we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 72 publications
3
78
0
1
Order By: Relevance
“…Our finding that HAI1-AHL10 signaling regulated JA metabolism (AOS and AOC1) and JA responsive (JR2, VSP2) genes suggests that HAI1 also has a feedback effect on JA. This result is also consistent with other reports of cross-regulation between JA and ABA metabolism (57). In our previous characterization of HAI1, we noted that hai1-2 had altered expression of many defense-related genes and concluded that HAI1 could be involved in tradeoffs between pathogen defense and drought response (15).…”
Section: The Growth Assays Gene Expression Analysis and Localizationsupporting
confidence: 92%
“…Our finding that HAI1-AHL10 signaling regulated JA metabolism (AOS and AOC1) and JA responsive (JR2, VSP2) genes suggests that HAI1 also has a feedback effect on JA. This result is also consistent with other reports of cross-regulation between JA and ABA metabolism (57). In our previous characterization of HAI1, we noted that hai1-2 had altered expression of many defense-related genes and concluded that HAI1 could be involved in tradeoffs between pathogen defense and drought response (15).…”
Section: The Growth Assays Gene Expression Analysis and Localizationsupporting
confidence: 92%
“…However, Thompson et al . () suggested that possible disruptions of JA signaling might be the cause of the observed developmental changes in the rbl10 mutants and there is an increasing body of work demonstrating a relationship between chloroplast glycerolipid metabolism and JA biosynthesis (Lin et al ., ; Wang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Phytohormone analysis was performed using 4‐week‐old WT, rbl10‐ 1, and rbl10‐ 2 plant leaves wounded with a hemostat and extracts prepared and quantified essentially as described in Wang et al ., ; (Wang et al ., ). Time points were collected as follows: before wounding, 20 min after wounding, and 60 min after wounding.…”
Section: Methodsmentioning
confidence: 99%
“…For example, JAM1 regulates both ABA and JA responses in Arabidopsis (Li et al ., ; Nakata et al ., ). ABA could promote the expression of PLIP2 and PLIP3, which might be involved in initiating JA biosynthesis (Wang et al ., ). In this study, we reveal two mechanisms underlying the crosstalk between JA and ABA: JAZ proteins can physically interact with ABI5 and repress its activity; ABA can induce JA biosynthesis to promote the degradation of JAZ proteins.…”
Section: Discussionmentioning
confidence: 97%